THE STARTUP OWNER'S MANUAL. the Step-by-Step Guide for Building a Great Company - Blank, Steven G. (Steven Gary), author 632757; Dorf, Bob, author 632758 (Hoboken, New Jersey : John Wiley & Sons, Inc., 2020)
The Startup Owner's Manual guides you, step-by-step, as you put the Customer Development process to work. This method was created by renowned Silicon Valley startup expert Steve Blank, co-creator with Eric Ries of the "Lean Startup" movement and tested and refined by him for more than a decade. This 608-page how-to guide includes over 100 charts, graphs, and diagrams, plus 77 valuable checklists that guide you as you drive your company toward profitability. It will help you:• Avoid the 9 deadly sins that destroy startups' chances for success• Use the Customer Development method to bring your business idea to life• Incorporate the Business Model Canvas as the organizing principle for startup hypotheses• Identify your customers and determine how to "get, keep and grow" customers profitably• Compute how you'll drive your startup to repeatable, scalable profits.